Structure elucidation of active compounds from Coffea canephora Pierre ex A.Froehner cascara and their potential as anticancer against breast cancer cells - Novi Fajar Utami; Berna Elya; Hayun; Kusmardi Kusmardi (GarVal Editorial Ltda., 2024)
Context: One approach to cancer therapy medication is exploring medicinal plants that contain one or more compounds specifically targeting cancer cells with fewer side effects. Cascara from coffee fruit (Coffea canephora Pierre ex A.Froehner) is a waste rarely processed but has various chemical contents that can be used in medicine. Aims: To evaluate the in silico and in vitro activity of compounds isolated from ethanolic extract of C. canephora cascara against HeLa and MCF-7 breast cancer cells. Methods: Isolation of the compounds by radial chromatography and thin layer chromatography techniques, and the chemical structures were elucidated by infrared radiation, ultraviolet, nuclear magnetic resonance spectroscopy, and mass spectrometry. In silico study about the compounds binding with the receptor responsibility to cancer (caspases 3 and 9). In vitro study by examining the cytotoxicity of HeLa and MCF-7 cells of the isolated compounds from C. canephora. Results: Four known bioactive compounds, lupeol (1), stigmasterol (2), ursolic acid (3), and caffeic acid (4), were isolated from the ethanol extract of C. canephora cascara. Based on the ESI-MS results, the m/z value for lupeol was 427.50 [M+H]+, stigmasterol was 454.48 [M+ACN+H]+, ursolic acid was 456.51 [M+H]+, and caffeic acid was 179 [M-H]. In silico and in vitro data show that the ursolic acid compound has activity against HeLa and MCF-7 cancer cells with IC50 values of 25.98 ± 0.01 µg/mL and 12.70 ± 0.11 µg/mL, respectively. Conclusions: All isolated compounds from C. canephora cascara have a promising ability to interact with caspases 3 and 9, particularly ursolic acid, which has the smallest IC50 value against HeLa and MCF-7 breast cancer cells.